PENGARUH PENAMBAHAN TRACE METAL (MOLYBDENUM & SELENIUM) TERHADAP PEMBUATAN BIOGAS DARI SAMPAH ORGANIK DAN KOTORAN SAPI - Fatimah, Grace Angelin (Universitas Sumatera Utara, 2017)
Trace metal are essential for the enzyme cofactors in methane formation, but its availability of natural is not enough so that the necessary additional trace metal. The purpose of this study is to determine the effect of addition Molybdenum (Mo) and Selenium (Se) as trace metal on the quality and quantity of biogas in anaerobic digesters. The study was carried out by mixing vegetables wastes, aquadest and cow manure that have been in a blender and then have been fermented for 30 days in variety of addition of trace metal Mo 10 mg/L, Se 10 mg/L and a mixture of Mo + Se 10 mg/L in an reactor batch of 4 L capacity. Operation in digesters, pH was maintained in range (6.5 – 8) and at temperature 25 – 30 oC. This research parameters that observed were volume biogas, pH, temperature, TS and VS. The highest of volume cumulative biogasin this experiment 630 ml are formed Mo + Se, with degradation average TS 26.69 % and VS 17.18 %.